2002
DOI: 10.1002/1521-3803(20020301)46:2<64::aid-food64>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bottle colour and storage conditions on browning of orange wine

Abstract: We investigated the effect of bottle colour, storage temperature and storage time on the browning of orange wine. Kozan orange variety was used for the production of wine. The fermentation was performed spontaneously at 20 degrees C. The wine was bottled in three differently coloured bottles: clear white, green and brown. Then each was divided into two parts: one part was stored at 13-14 degrees C in the cellar and the other at 23-26 degrees C in the laboratory for 150 days. During the storage, browning index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 12 publications
3
23
0
3
Order By: Relevance
“…One study on fino wines exposed to a 1500 W lamp showed that losses of phenolic compounds were greater in clear (transparent) glass, but greater colour development (420 absorbance) occurred for wines in topaz bottles [14]. An alcohol beverage made from oranges was stored in clear, green and brown bottles [15]. A higher browning index was observed with clear bottles, but a phenolic analysis was not performed.…”
Section: Abbreviationsmentioning
confidence: 99%
“…One study on fino wines exposed to a 1500 W lamp showed that losses of phenolic compounds were greater in clear (transparent) glass, but greater colour development (420 absorbance) occurred for wines in topaz bottles [14]. An alcohol beverage made from oranges was stored in clear, green and brown bottles [15]. A higher browning index was observed with clear bottles, but a phenolic analysis was not performed.…”
Section: Abbreviationsmentioning
confidence: 99%
“…En cuanto a los vinos cítricos, los conocimientos más actualizados que se tienen sobre su elaboración son de Turquía y los países asiáticos (China, Japón, Corea), entre los cuales se pueden citar los estudios sobre la producción de vino de naranja realizados por Arici and Yuecel, (1994) en China; el aislamiento e identificación de levaduras para la producción de vino de naranja de Young-Hwan- Ko et al (1997) en Corea; estudios básicos de las técnicas de producción de vino de naranja de Yuo-YoungWang and Guo-Qing-He (2000) en China; estudios de los componentes del flavor en vinos de naranjas variedad Kozan y el efecto del color de las botellas y las condiciones de almacenamiento sobre el amarronado de vino de naranja, ambos de Selli et al (2002Selli et al ( -2003 en Turquía.…”
Section: I3 Antecedentes De Elaboración De Vinos De Frutasunclassified
“…De acuerdo a Selli et al (2002), estos índices se ven afectados no sólo por el tiempo de almacenamiento sino por el color del envase que permite la transmisión de luz de baja longitud de onda por ende de alta energía que favorecen reacciones químicas de oscurecimiento, tal como la oxidación del ácido ascórbico. Es de hacer notar que el ensayo se hizo en aerobiosis lo cual potencia estas reacciones.…”
Section: 323-indice De Amarronadounclassified
See 1 more Smart Citation
“…Light exposure after bottling may also affect constituents of alcoholic beverages, particularly 350 nm-500 nm wavelengths (D'Auria et al 2003). Clear, green and amber are common wine bottle hues, and transmit 95%, 50%, and 10% of 350 nm-550 nm light, respectively (Selli et al 2002). Additionally, temperature may also affect bottle-ageing through mediation of reaction rates, with higher storage temperatures producing "quickageing" effects associated with advanced oxidation, and altering volatile composition (Marais & Pool 1980).…”
Section: Introductionmentioning
confidence: 99%